PENGARUH NILAI TUKAR DAN STABILITAS TERHADAP HARGA SAHAM (Studi pada Perusahaan Food And Beverage di BEI Tahun 2009-2018) - Nurul Fauziyah; Siti Shoimah (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2020)
Stock is the owner of the company, the greater the shares it has, the greater the power of a company. The purpose of this study was to determine the effect of exchange rates and stability on stock prices in food and beverage manufacturing companies on the Indonesia Stock Exchange in the 2009-2018 period. The research method used in this study is the method of multiple linear regression. The population in this study were 7 food and beverage companies. The sample collection technique used in this study was purpive sampling technique which numbered 18 food and beverage companies. The results of this study indicate that the exchange rate has a negative and not significant effect on stock prices. Variable stability to stock prices from the first year to the fifth year rose significantly. But starting the following year, namely the sixth year, it fell evenly or insignificantly. Because it is known from the results of the histogram dependent stock price increase is not stable. All independent variables, namely the exchange rate and stability, do not simultaneously influence the dependent variable, namely the stock price.